The statistical analysis of IEEE 802.11 wireless local area network–based received signal strength indicator in indoor location sensing systems - Yan Wang; Min Li; Mu Li (International Journal of Distributed Sensor Networks)
Global positioning system is an important space information network for location service. However, the satellite signal is attenuated or even blocked in indoor environment. To make up for the defect of global positioning system, IEEE 802.11 wireless local area network (Wi-Fi) infrastructure is proposed to relay the task of positioning in indoor scenario with their superiority of being widely deployed. In Wi-Fi indoor localization application, received signal strength indicator is the most prevalent parameter. From the former literature, it was supposed to be Gaussian distribution. In this article, we first formulate the received signal in a multipath channel based on the IEEE 802.11 standard, then we derive the probability density function of received signal strength indicator and it is proved to be a noncentral Chi-square distribution. Finally, the correctness of the distribution is verified from the aspect of noncentral parameter in an experiment system.